ГАРМОНІЗАЦІЯ ІНТЕЛЕКТУАЛЬНОГО Й ЕМОЦІЙНОГО В ПІДВИЩЕННІ ЕФЕКТИВНОСТІ УРОКУ В СУЧАСНІЙ ШКОЛІ (Педагогіка вищої та середньої школи, 2008)
The article deals with possibilities of interaction of intellectual and motional factors of the modern lesson in providing quality education for students.